Domperidone Inhibits Clostridium botulinum C2 Toxin and Bordetella pertussis Toxin - Jinfang Jia; Maria Braune-Yan; Stefanie Lietz; Mary Wahba; Arto T. Pulliainen; Holger Barth; Katharina Ernst (Toxins, 2023)
Bordetella pertussis toxin (PT) and Clostridium botulinum C2 toxin are ADP-ribosylating toxins causing severe diseases in humans and animals. They share a common translocation mechanism requiring the cellular chaperones Hsp90 and Hsp70, cyclophilins, and FK506-binding proteins to transport the toxins’ enzyme subunits into the cytosol. Inhibitors of chaperone activities have been shown to reduce the amount of transported enzyme subunits into the cytosol of cells, thus protecting cells from intoxication by these toxins. Recently, domperidone, an approved dopamine receptor antagonist drug, was found to inhibit Hsp70 activity. Since Hsp70 is required for cellular toxin uptake, we hypothesized that domperidone also protects cells from intoxication with PT and C2. The inhibition of intoxication by domperidone was demonstrated by analyzing the ADP-ribosylation status of the toxins’ specific substrates. Domperidone had no inhibitory effect on the receptor-binding or enzyme activity of the toxins, but it inhibited the pH-driven membrane translocation of the enzyme subunit of the C2 toxin and reduced the amount of PTS1 in cells. Taken together, our results indicate that domperidone is a potent inhibitor of PT and C2 toxins in cells and therefore might have therapeutic potential by repurposing domperidone to treat diseases caused by bacterial toxins that require Hsp70 for their cellular uptake.